Youth film in Russia and Serbia since the 1990s - Todd, Laura J. (2016)
This thesis explores the youth film genre in Russia and Serbia since the 1990s. Youth film is not only an essential means of tracing changes in cultural perceptions about young people and their lives in the post-communist period, but I argue that the genre serves as a means of representing society as a whole. The youth film genre, as an overarching framework dictated by the age of a film’s protagonists, encompasses and adopts a wide variety of sub-genres. This flexibility in youth film allows for an innovative study of the position of one genre as part of a wider sphere of genre film-making in the post-communist period.